Polarized Macrophages in Periodontitis: Characteristics, Function, and Molecular Signaling - Sun, Xiaoyu; Gao, Jike; Meng, Xiang; Lu, Xiaoxuan; Zhang, Lei; Chen, Ran (Frontiers in Immunology, 2021)
Periodontitis (PD) is a common chronic infectious disease. The local inflammatory response in the host may cause the destruction of supporting periodontal tissue. Macrophages play a variety of roles in PD, including regulatory and phagocytosis. Moreover, under the induction of different factors, macrophages polarize and form different functional phenotypes. Among them, M1-type macrophages with proinflammatory functions and M2-type macrophages with anti-inflammatory functions are the most representative, and both of them can regulate the tendency of the immune system to exert proinflammatory or anti-inflammatory functions. M1 and M2 macrophages are involved in the destructive and reparative stages of PD. Due to the complex microenvironment of PD, the dynamic development of PD, and various local mediators, increasing attention has been given to the study of macrophage polarization in PD. This review summarizes the role of macrophage polarization in the development of PD and its research progress.